Dexmedetomidine attenuates lipopolysaccharide-induced acute lung injury by inhibiting oxidative stress, mitochondrial dysfunction and apoptosis in rats - Fu, Chunlai (Mol Med Rep, 2017)
Previous studies have identified that dexmedetomidine (DEX) treatment can ameliorate the acute lung injury (ALI) induced by lipopolysaccharide and ischemia-reperfusion. However, the molecular mechanisms by which DEX ameliorates lung injury remain unclear. The present study investigated whether DEX, which has been reported to exert effects on oxidative stress, mitochondrial permeability transition pores and apoptosis in other disease types, can exert protective effects in lipopolysaccharide (LPS)-induced ALI by inhibiting oxidative stress, mitochondrial dysfunction and mitochondrial-dependent apoptosis. It was revealed that LPS-challenged rats exhibited significant lung injury, characterized by the deterioration of histopathology, vascular hyperpermeability, wet-to-dry weight ratio and oxygenation index (PaO(2)/FIO(2)), which was attenuated by DEX treatment. DEX treatment inhibited LPS-induced mitochondrial dysfunction, as evidenced by alleviating the cellular ATP and mitochondrial membrane potential in vitro. In addition, DEX treatment markedly prevented the LPS-induced mitochondrial-dependent apoptotic pathway in vitro (increases of cell apoptotic rate, cytosolic cytochrome c, and caspase 3 activity) and in vivo (increases of |terminal deoxynucleotidyl transferase dUTP nick-end labeling positive cells, cleaved caspase 3, Bax upregulation and Bcl-2 downregulation). Furthermore, DEX treatment markedly attenuated LPS-induced oxidative stress, as evidenced by downregulation of cellular reactive oxygen species in vitro and lipid peroxides in serum. Collectively, the present results demonstrated that DEX ameliorates LPS-induced ALI by reducing oxidative stress, mitochondrial dysfunction and mitochondrial-dependent apoptosis.